The Franchising of Pesantren Education: A New Model of The Development of Islamic Education in A Disruptive Era - Nurul Azizah; Syamsul Ma'arif; Mahfud Junaedi (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
This study aims to find a new model in the development of Islamic Boarding Schools or well known as pesantren. By adopting a business system, pesantren can be developed by a franchise model. The data collection methods used in this study were interviews, observation, and documentation. From the data obtained, the results indicated a new model in the development of pesantren, namely the franchise model. The franchise model in pesantren can be perceived in three points. Firstly, the existence of the central pesantren as the control holder of branch pesantren. Secondly, the presence of royalties paid by the branch pesantren to the central pesantren in exchange for the given learning system. The royalty is not material but in the form of tahfidz students who have good character. It is in line with the purpose of the Tahfidz Daarul Qur’an Islamic Boarding School to print thousands of memorizers of the Qur’an in the archipelago. Thirdly, the existence of a standard learning system that can be adopted and followed by the branch pesantren.